2013
DOI: 10.1002/acr.22128
|View full text |Cite
|
Sign up to set email alerts
|

Is the Severity of Knee Osteoarthritis on Magnetic Resonance Imaging Associated With Outcome of Exercise Therapy?

Abstract: Objective. To evaluate associations between severity of knee osteoarthritis (OA) on magnetic resonance imaging (MRI) and treatment outcomes in knee OA patients treated with exercise therapy in an exploratory study. Results. Improvements of 24%, 34%, and 21% on average in activity limitations, pain, and muscle strength, respectively, after 12-week exercise therapy were found (P < 0.001). Severity of abnormalities in PF cartilage integrity was significantly associated with fewer improvements in both activity lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…35,37,38,46 In a recent publication on the benefits of exercises on OA it was suggested that all grades of OA severity can benefit from professionally supervised exercise therapy. 30 Resistance exercise has been shown to be effective in pain reduction and improving physical functional activity. This mode of exercise may restore muscle strength and joint mechanics while improving physical function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,37,38,46 In a recent publication on the benefits of exercises on OA it was suggested that all grades of OA severity can benefit from professionally supervised exercise therapy. 30 Resistance exercise has been shown to be effective in pain reduction and improving physical functional activity. This mode of exercise may restore muscle strength and joint mechanics while improving physical function.…”
Section: Discussionmentioning
confidence: 99%
“…It is a reliable and valid outcome measure for evaluation of patients with hip and knee OA. 19,29,30 Each patient was asked to give his or her response to pain intensity measures (5 items), joint stiffness (2 items), and physical function (17 items) through a 5-point scale (0-4, where: 0 = no pain/limitation; 1 = mild pain/limitation; 2 = moderate pain/limitation; 3 = severe pain/limitation; and 4 = extreme pain/limitation). Its maximal scores for pain, stiffness, and physical functions are 20, 8, and 68, respectively.…”
Section: Physical Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taechaarpornkul et al conducted a comparison between 2-point and 6-point EA in each lap in order to preliminarily investigate whether the number of points significantly affects the efficacy of EA [20]. Moreover, the response of advanced KOA to the same treatment appeared to be less desirable than that of lower-level KOA [21]. Hence, it could be suspected that efficacy exerted by distinct points of EA on KOA could vary with severity of KOA, thereby necessitating a study to profoundly describe how the efficacy of EA of diverse points is related to different stages of KOA.…”
Section: Introductionmentioning
confidence: 99%
“…10 Whatever the grade of the disease, there is enough published data to show that exercise therapy has some beneficial effect. A study by Knoop et al 11 has revealed that effectiveness of exercise therapy is independent of the MRI evaluated severity of OA, and thus becomes an important tool in the armamentarium of medical personnel in managing this disorder. Despite the fact that exercise therapy is an important aspect of conservative treatment of the disease, designing an exercise rehabilitation program for individual patients is often a challenge, as each patient may require a personally tailored program that best suits them.…”
mentioning
confidence: 99%